Prolonged Intestinal Transit Time and Its Relation with Capsule Endoscopy Diagnostic Yield - Juan Lasa,; Gustavo Cernadas,; Pablo A. Olivera,; Rafael Moore, (Turkish Journal of Gastroenterology, 2022)
Background: Capsule endoscopy is a gold standard diagnostic method for small bowel lesions. There is scarce evidence regarding vari- ables that may increase the odds of identifying small bowel lesions with this endoscopic method. The aim of this work is to describe variables associated with a higher probability of finding small bowel lesions on capsule endoscopy.Methods: Cross-sectional study was performed using our Department’s adult patients’ capsule endoscopy database. The presence of any small bowel mucosal lesion was registered. Other variables were examined: age, gender, reason for referral, quality of bowel cleans- ing, and intestinal transit time. These variables were compared between those patients showing at least 1 lesion versus those without lesions. Univariate and multivariate analysis was performed to determine variables significantly associated with the presence of bowel lesions.Results: In total, 140 studies were analyzed; 90% were performed due to occult gastrointestinal bleeding. Median age was 69 years (60-75); 54.29% were males. Bowel cleansing was adequate in 94.29%; 68.57% showed at least 1 lesion. Non-significant difference was observed in terms of age between groups of comparison (70 [61-76] vs 63 [59-74], P = .07). No difference was found comparing bowel cleansing, gender, or reason for referral. Intestinal transit time was significantly longer among those patients with a bowel lesion (359 minutes [257-427] vs 279 minutes [200-333], P = .05). On multivariate analysis, age and intestinal time were significantly associ- ated with the presence of at least one small bowel lesion (odds ratio 1.02 [1-1.06] and 1.09 [1.03-1.12], respectively).Conclusion: Age and intestinal transit time were significantly associated with the presence of abnormal findings on capsule endoscopy.Cite this article as: Lasa J, Cernadas G, Olivera PA, Moore R. Prolonged intestinal transit time and its relation with capsule endoscopy diagnostic yield. Turk J Gastroenterol. 2022;33(6):520-524.